A reading enrichment program for gifted adolescent - Morales Silva, Silvia (2008)
This descriptive research examines the performance on reading comprehension of four gifted adolescents participating in a reading enrichment program. This performance is related to the variables associated to the gifted performance following the model developed by Mönks: motivation, creativity, high ability, school, peers and family. Results showed that school does not satisfy the cognitive needs of these students and it does not offer the required social support either. The family provides the main social support. The motivation, creativity, the high level of language and concentration of the participants facilitate learning. The reading program is described by the participants as motivating due to the subject-matters and methodology; furthermore, due to the opportunity to deal with peers who have a similar cognitive level.